Legitimação democrática do poder judiciário para a função normativa com eficácia vinculante: a participação necessária de atores sociais nas ações com potencial repetitivo - Welsch, Gisele Mazzoni (2015)
This work deals with the jurisdiction of regulatory function from the observance of decision-making criteria as a way of enforcing rights and guarantees in the reality of democratic state. To defend the viability of judicial creation of law as a way of granting equality of treatment to similar cases and legal certainty, however avoiding the risks of judicial arbitrariness. Firstly identifies the phenomenon of judicial creation and analyzes the development of the judicial function, especially in the common law system, which served as a model linking the judicial precedents, influencing progressively to the civil law system configuration, especially faced with the reality and demands of the democratic rule of law (Constitutional State). Law standardization techniques faced with binding character present in the Brazilian legal system, establishing the relationship with the normative function of Jurisdiction, from obtaining the constitutionally appropriate response and through adequate motivation of judicial decisions, made with compliance due to decisional criteria of participation and necessary intervention of specialized organ in cases with repetitive potential as a way of granting democratic legitimacy and ensure rationality and legal certainty to the jurisdictional activity.